The critical role of Golgi cells in regulating spatio-temporal integration and plasticity at the cerebellum input stage - D‘Angelo, Egidio (Frontiers in Neuroscience, 2008)
After the discovery at the end of the 19th century (Golgi, 1883), the Golgi cell was precisely described by S.R. y Cajal (see Cajal, 1987, 1995) and functionally identified as an inhibitory interneuron 50 years later by J.C. Eccles and colleagues (Eccles e al., 1967). Then, its role has been casted by Marr (1969) within the Motor Learning Theory as a codon size regulator of granule cell activity. It was immediately clear that Golgi cells had to play a critical role, since they are the main inhibitory interneuron of the granular layer and control activity of as many as 100 millions granule cells. In vitro, Golgi cells show pacemaking, resonance, phase-reset and rebound-excitation in the theta-frequency band. These properties are likely to impact on their activity in vivo, which shows irregular spontaneous beating modulated by sensory inputs and burst responses to punctuate stimulation followed by a silent pause. Moreover, investigations have given insight into Golgi cells connectivity within the cerebellar network and on their impact on the spatio-temporal organization of activity. It turns out that Golgi cells can control both the temporal dynamics and the spatial distribution of information transmitted through the cerebellar network. Moreover, Golgi cells regulate the induction of long-term synaptic plasticity at the mossy fiber - granule cell synapse. Thus, the concept is emerging that Golgi cells are of critical importance for regulating granular layer network activity bearing important consequences for cerebellar computation as a whole.